Relevansi Pendidikan Kewarganegaraan dalam Membangun Karakter Unggul Generasi Muda Menuju Indonesia Emas - Seriwati Ginting (Ideas Publishing, 2026)
The nation's noble values are beginning to fade, and a shift is occurring. The purpose of this study is to rediscover the urgency of balancing the rights and obligations of citizens. The method used is a mixed method for comprehensive results. This study found that the fading of civic education values is caused by several factors, which are interconnected. Students need figures who can serve as role models. Students are skeptical of national values, integrity, and nationalism. The implications of this study make every element of society aware that realizing the nation's noble values does not stand alone; it must support each other for the realization of the superior character of the younger generation.